Model sistem Pakar Pendiagnosis Penyakit Pada Sapi Dengan Metode Certainty Factor - Exalthya Sera; Fadilah Fadilah; Bahar Bahar (STMIK Banjarbaru, 2025)
Limited access to veterinary health services, farmers’ lack of knowledge, and the high cost and time required for consultations are major obstacles in handling cattle diseases, especially in remote areas. These issues often lead to delays in diagnosis and treatment, resulting in significant economic losses. This study proposes the development of a computer-based expert system using the Certainty Factor method as a solution to assist farmers in independently diagnosing cattle diseases. The system is equipped with its main feature, a diagnosis process, as well as a chat feature for direct consultation with veterinarians as a novelty element. Testing was conducted on 19 test data by comparing the system’s diagnostic results with those of experts, showing a match rate of 84.21% and 15.79% mismatch due to symptom similarities and differences in severity interpretation. The results demonstrate that the system has fairly good accuracy and is suitable for use as an early diagnostic tool, which is expected to accelerate disease handling and reduce farmers’ economic losses.Keywords: Expert System; Certainty Factor; Cattle Disease Diagnosis; Veterinary Consultation Chat. AbstrakKeterbatasan akses layanan kesehatan hewan, minimnya pengetahuan peternak, serta biaya dan waktu yang tinggi untuk konsultasi menjadi hambatan dalam penanganan penyakit sapi, khususnya di daerah terpencil. Permasalahan ini kerap mengakibatkan keterlambatan diagnosis dan penanganan, sehingga menimbulkan kerugian ekonomi yang signifikan. Penelitian ini mengusulkan pengembangan sistem pakar berbasis komputer menggunakan metode Certainty Factor sebagai solusi untuk membantu peternak mendiagnosis penyakit sapi secara mandiri. Sistem ini dilengkapi dengan fitur utamanya proses diagnosis, serta fitur chat untuk konsultasi langsung dengan dokter hewan sebagai unsur kebaruan. Pengujian dilakukan pada 19 data uji dengan membandingkan hasil diagnosis sistem dan pakar, menunjukkan tingkat kesesuaian sebesar 84,21% dan 15,79% tidak sesuai akibat kemiripan gejala serta perbedaan interpretasi tingkat keparahan. Hasil ini membuktikan bahwa sistem memiliki akurasi yang cukup baik dan layak digunakan sebagai alat bantu diagnosis awal, yang diharapkan dapat mempercepat penanganan penyakit dan mengurangi kerugian ekonomi peternak.Kata kunci: Sistem Pakar; Certainty Factor; Diagnosis Penyakit Sapi; Chat Konsultasi Dokter Hewan.